2019
DOI: 10.3892/etm.2019.8175
|View full text |Cite
|
Sign up to set email alerts
|

miR‑190b promotes colorectal cancer progression through targeting forkhead box protein P2

Abstract: microRNA-190b (miR-190b) is abnormally expressed in multiple types of cancer, however, its role in colorectal cancer (CRC) is largely unknown. In the present study, it was demonstrated that miR-190b expression was upregulated in CRC cell lines compared with the normal epithelial colon cell line. Knockdown of miR-190b decreased proliferation, colony formation and invasion, and increased apoptosis of CRC cells. Furthermore, forkhead box protein P2 (FOXP2) was predicted as a target of miR-190b and further validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the present study, we identified 126 miRNAs downregulated by DDX17 suppression in SW620 cells, including miR-190b, miR-542-5p and miR-301a-3p. MiR-190b exhibited an oncogenic function in CRC and bladder cancer [ 32 , 33 ]. Increased expression of miR-542-5p was observed in the plasma of CRC patients compared with non-CRC subjects, and was associated with abnormal purine metabolism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified 126 miRNAs downregulated by DDX17 suppression in SW620 cells, including miR-190b, miR-542-5p and miR-301a-3p. MiR-190b exhibited an oncogenic function in CRC and bladder cancer [ 32 , 33 ]. Increased expression of miR-542-5p was observed in the plasma of CRC patients compared with non-CRC subjects, and was associated with abnormal purine metabolism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identi ed 127 miRNAs downregulated by DDX17 suppression in SW620 cells, including miR-190b, miR-542-5p and miR-301a-3p. MiR-190b exhibited an oncogenic function in CRC and bladder cancer 32,33 . Increased expression of miR-542-5p was observed in the plasma of CRC patients compared with non-CRC subjects, and was associated with abnormal purine metabolism 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, miR-375 acts as tumor suppressor, repressing many critical oncogenes such as PDK1, JAK2, IGF1R, and AEG-1 [ 34 ]. Less known, is miR-190b, although it is also engaged in promoting many cancers such as bladder carcinoma [ 35 ] or colorectal cancer [ 36 ] and found, as well, as a novel tumor suppressor in lung cancer during in vivo miRNA knockout screening [ 37 ].…”
Section: Discussionmentioning
confidence: 99%